An estimate of the number of tropical tree species - Slik, J W Ferry; Arroyo-Rodríguez, Víctor; Aiba, Shin-Ichiro; Alvarez-Loayza, Patricia; Alves, Luciana F; Ashton, Peter; Balvanera, Patricia; Bastian, Meredith L; Bellingham, Peter J; van den Berg, Eduardo; Bernacci, Luis; da Conceição Bispo, Polyanna; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
The high species richness of tropical forests has long been recognized, yet there remains substantial uncertainty regarding the actual number of tropical tree species. Using a pantropical tree inventory database from closed canopy forests, consisting of 657,630 trees belonging to 11,371 species, we use a fitted value of Fisher's alpha and an approximate pantropical stem total to estimate the minimum number of tropical forest tree species to fall between ∼ 40,000 and ∼ 53,000, i.e., at the high end of previous estimates. Contrary to common assumption, the Indo-Pacific region was found to be as species-rich as the Neotropics, with both regions having a minimum of ∼ 19,000-25,000 tree species. Continental Africa is relatively depauperate with a minimum of ∼ 4,500-6,000 tree species. Very few species are shared among the African, American, and the Indo-Pacific regions. We provide a methodological framework for estimating species richness in trees that may help refine species richness estimates of tree-dependent taxa.